Ensino de conceitos básicos de Termodinâmica utilizando um motor de combustão interna - Mateazzo, Alexandre Sbrissa (2022)
The development of technology has introduced significant changes in our lives, such as in communication, economy, transport, entertainment, even in education. Currently, students and teachers are faced with challenges that can significantly change the way we learn and teach science. In the teaching of Physics, which is a science whose methodologies are experimentation, observation and mathematical analysis, it is impossible to ignore the tremendous impact that technology can have on new generations of students. In this work we explore the use of technology, by using a real internal combustion engine, properly prepared to be used as teaching material, to teach basic concepts of Thermodynamics such as heat, work, temperature, energy, entropy, the Laws of Thermodynamics, thermal engines, processes and thermodynamic cycles, among others, for high school students. Our educational product consists of a tutorial containing all the details for the preparation of a scrapped engine to be used in the classroom and a suggestive didactic sequence for the discussion of the proposed theme, explaining the operation of the engine through the ideal Otto cycle. The application of the product in the classroom was divided into 3 activities developed in 4 lessons of 45 minutes. Initially we made a general discussion on the subject using an open-ended questionnaire containing three guiding questions to explore the students' prior knowledge. Then, the proposed topics were developed through discussions and calculations, all complemented by demonstrations using the real engine. The activities were closed with a multiple choice questionnaire covering the main topics of Thermodynamics worked on. The product was applied to 2nd year high school students from a public school located in Itu city, municipality of São Paulo. It was very well received by the students and all the proposed topics could be widely discussed in the allotted time in a satisfactory manner.